Effectiveness Of E-Government Implementation In Public Services In The Land Office Of Semarang City - Prayogo, Widodo (CV. Inara, 2022)
The development of increasingly sophisticated information technology requires that the public service system must be upgraded to an electronic system. One way is to implement the E-Government system in realizing electronic-based government. The E-Government system is intended to make government administration easier, faster, transparent, and effective. The E-Government system is determined by the principles of good governance, such as law enforcement, efficiency and effectiveness of state administration, public participation and justice. The implementation of the system involves human resources who can support the application of the system and also provide information to the public regarding the use of the E-Government system. Legal regulations related to the E-Government system have been stated in Presidential Instruction Number 3 of 2003 concerning National Policies and Strategies for E-Government Development, where the rapid advancement of communication and information technology and the potential for its widespread use can open up access, management and utilization of information in capacity. large ones quickly and accurately. This study uses a normative juridical approach which analyzes the results of research in the field with applicable legal regulations. A qualitative approach is used to emphasize the aspect of in-depth understanding of a problem. The purpose of this paper is to determine the implementation of the E-Government system in public services at the Semarang City Land Office, Of course, since the pandemic, the E-Government system can be a solution in terms of public services, given the limitations of the public to come directly. The implementation cannot be separated from the obstacles that occur, so it can be seen the obstacles and the solutions provided so that the use of the E-Government system can be even better.